2010
DOI: 10.1016/j.atherosclerosis.2009.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Clear detection of ADIPOQ locus as the major gene for plasma adiponectin: Results of genome-wide association analyses including 4659 European individuals

Abstract: Objective-Plasma adiponectin is strongly associated with various components of metabolic syndrome, type 2 diabetes and cardiovascular outcomes. Concentrations are highly heritable and differ between men and women. We therefore aimed to investigate the genetics of plasma adiponectin in men and women.Methods-We combined genome-wide association scans of three population-based studies including 4659 persons. For the replication stage in 13795 subjects, we selected the 20 top signals of the combined analysis, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
164
3
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(194 citation statements)
references
References 36 publications
21
164
3
6
Order By: Relevance
“…Very weak linkage disequilibrium exists between rs7195409 and rs3865188 (r 2 ¼ 0, D ′ ¼ 0.12 in CEU and r 2 ¼ 0, D ′ ¼ 0.06 in CHB and JPT combined samples), and conditional analyses further supported their independence (P for rs3865188 conditional on rs7195409 ¼ 5.0 × 10 216 ; P for rs7195409 conditional on rs3865188 ¼ 0.11). In addition, for the CDH13 variant rs11646213, which was previously reported in a study of 4659 European individuals (P ¼ 0.10), we observed stronger association in the 1776 CLHNS mothers (P ¼ 1.27 × 10 26 ) (29). Together, these results suggest that a difference in genetic architecture between Europeans and…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Very weak linkage disequilibrium exists between rs7195409 and rs3865188 (r 2 ¼ 0, D ′ ¼ 0.12 in CEU and r 2 ¼ 0, D ′ ¼ 0.06 in CHB and JPT combined samples), and conditional analyses further supported their independence (P for rs3865188 conditional on rs7195409 ¼ 5.0 × 10 216 ; P for rs7195409 conditional on rs3865188 ¼ 0.11). In addition, for the CDH13 variant rs11646213, which was previously reported in a study of 4659 European individuals (P ¼ 0.10), we observed stronger association in the 1776 CLHNS mothers (P ¼ 1.27 × 10 26 ) (29). Together, these results suggest that a difference in genetic architecture between Europeans and…”
Section: Discussionsupporting
confidence: 73%
“…0.8 across ADIPOQ and its flanking regions, observed that adiponectin level was significantly associated with SNPs in two different regulatory regions, the 5 ′ -promoter (rs17300539) and the 3 ′ -untranslated regions (rs6773957) (17). A recent study dissecting the genetic architecture of plasma adiponectin suggested that two ADIPOQ variants (rs17300539 and rs182052) exhibited independent association (18), and a recent GWAS of 4659 European individuals suggested association with at least nine SNP groups near ADIPOQ (29) Fig. S2), although none of the SNPs imputed with high quality perfectly tags the strongly associated rs11924390 -rs864265 haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the ADIPOQ gene on the risk of obesity and MetS may vary according to ethnicity, age and the degree of obesity across populations (47). Some studies indicate that ADIPOQ variants may contribute to MetS and its components (12,20,36,48) while other reports point to the limited impact of ADIPOQ gene on MetS parameters (15,49). In this study, we found ADIPOQ promoter variants -11377C>G and -11391G>A, independently and as haplotypes that are associated with elevated blood lipids, central obesity and MetS.…”
Section: Discussionsupporting
confidence: 50%
“…23,37 Despite the strong association between adiponectin concentration and metabolic disorders described in various studies, other analyses have failed to detect a significant association between ADIPOQ variants and metabolic phenotype. 36,38 We also detected few associations between metabolic abnormalities and the selected variants of ADIPOQ that are present within genomic regions previously shown to be associated with metabolic phenotype. We had a power of 100% in the KING study to detect associations of ADIPOQ variants with metabolic abnormalities similar to those described by Iwashima et al 12 (assuming a¼0.05), but the previously observed association of Ile164Thr with hypertension was not replicated in our study.…”
Section: Adipoq Snps and Adiponectin Levelmentioning
confidence: 88%
“…36 Although we did not genotype rs17366568, rs1656930 is independent of this SNP (r 2 ¼0) in the HapMap database. Of the other eight SNPs, only rs822394 showed possible pairwise LD (r 2 ¼0.585) with rs1656930 in the HapMap database.…”
Section: Adipoq Snps and Adiponectin Levelmentioning
confidence: 99%